Quadriceps isometric strength as a predictor of exercise capacity in coronary artery disease patients. (29th August 2020) - Kamiya, Kentaro; Mezzani, Alessandro; Hotta, Kazuki; Shimizu, Ryosuke; Kamekawa, Daisuke; Noda, Chiharu; Yamaoka-Tojo, Minako; Matsunaga, Atsuhiko; Masuda, Takashi
Abstract: Background: Quadriceps strength is related to exercise capacity in normal subjects and different patient populations, but the relationship between maximal quadriceps isometric strength (QIS) and different exercise capacity levels in coronary artery disease (CAD) patients has not been systematically evaluated yet. Method: We studied 621 patients (60.6 ± 9.9 years, 538 males) with recent coronary artery bypass grafting or myocardial infarction, who underwent treadmill exercise testing, maximal QIS measurement (hand-held dynamometry), and coronary arteriography. Maximal QIS was expressed as absolute value (kg), %bodyweight, and %predicted maximum. Logistic regression was used to assess the relationship of maximal QIS, age, sex, number of diseased coronary vessels, peak systolic blood pressure, peak heart rate, brain natriuretic peptide, and left ventricular ejection fraction with 5, 7, and 10 estimated metabolic equivalents (eMETs) exercise capacity levels. Results: Maximal QIS %bodyweight was the strongest predictor of exercise capacity in each eMETs category. Receiver-operating characteristics curves identified maximal QIS of 46, 51, and 59 % bodyweight as the best predictive cut offs for 5, 7 and 10 eMETs, respectively, with positive predictive values of 0.72, 0.66, and 0.67, respectively. Conclusions: Maximal QIS is related with eMETs levels reached at exercise testing in CAD patients, and identified maximal QIS cut-off values for eMETs prediction may be used to set strength training goals according to patients' needs with regard to habitual physical activity level. Hand-held dynamometry may meet the need of easiness of use and low cost required for strength evaluation in large-scale clinical trials.